Qualitative and Quantitative Microbiological Studies of Paediatric Artemether-Lumefantrine Dry Powders and Paracetamol Syrups Obtained from Selected Drug Stores in Accra, Ghana - Solomon Opoku; Isaac Nyanor (Journal of Tropical Medicine)
Infants and children under five years generally have high susceptibility to pathogenic and opportunistic infections due to immaturity and inexperience of their immune responses. The lives of these young children are threatened when they consume pharmaceutical preparations of poor microbiological quality. Considering the widespread use of artemether-lumefantrine dry powder and paracetamol syrup among the general population in Ghana, there is a need to investigate the microbiological quality and safety of these paediatric pharmaceutical preparations. The study investigated the microbiological quality of 180 samples comprising 90 artemether-lumefantrine dry powders and 90 paracetamol syrups. The samples were tested for presence of specified indicator pathogens, Total Aerobic Microbial Count (TAMC), and Total Yeasts and Moulds Count (TYMC) using compendial procedures. Results from the study indicated that 16 (17.78%) of the paracetamol syrup samples showed bioburden levels above United States Pharmacopeia (USP) maximum acceptable limit, but none of the artemether-lumefantrine dry powder samples recorded microbial load above the limit of USP. Four samples of paracetamol syrup and 4 samples of artemether-lumefantrine dry powder showed presence of P. aeruginosa, whereas 5 samples of paracetamol syrup were found to be contaminated with Salmonella spp. Overall, 4.44% of the artemether-lumefantrine dry powders and 25.56% of the paracetamol syrups were found to be noncompliant with USP specifications for nonsterile pharmaceutical preparations for oral use. This study has revealed the existence of substandard paediatric pharmaceutical products in the Ghanaian market, hence the need for regulatory bodies to intensify monitoring and postmarketing surveillance programmes to help get rid of these products from the market.